Long-term outcomes in heritable thoracic aortic disease - Robertson, Elizabeth N.; Bannon, Paul G.; Jeremy, Richmond W. (Frontiers in Cardiovascular Medicine, 2022)
Heritable aortic aneurysm is an increasingly recognized cause of morbidity and mortality. Whilst Marfan syndrome (MFS) is well-known, the clinical presentation and prognosis of more newly described genetic syndromes is less familiar to clinicians. There is a particular lack of knowledge regarding clinical outcomes for non-syndromal heritable aortic disease. This study investigated the presentation, clinical course and survival of patients with syndromal [Loeys-Dietz, aneurysm-osteoarthritis, and aneurysm-cerebral arteriopathy (ACTA2) syndrome] and non-syndromal heritable aortic disease in comparison to MFS. The study group includes 536 individuals (283 Marfan, 176 non-syndromal heritable aortopathy, 36 aneurysm-osteoarthritis, 32 Loeys-Dietz, and 9 ACTA2 aneurysm) enrolled in a longitudinal clinical follow-up between 1990 and 2022. Age at diagnosis differed between groups: Marfan = 22.0 ± 16.6; Loeys-Dietz = 29.6 ± 21.5; aneurysm-osteoarthritis = 36.4 ± 18.8; ACTA2 aneurysm = 43.4 ± 18.6; non-syndromal heritable aortopathy = 47.2 ± 16.6 years (p < 0.001). Aortic dissection was the presenting event in 8% individuals with Marfan compared to 27% with non-syndromal heritable aortopathy and 34% with Loeys-Dietz syndrome (p < 0.01). Mean follow-up duration for the group was 16.4 years (range 0.2–30 years) and 74 individuals died during follow-up (Marfan = 52, Loeys-Dietz = 6, aneurysm-osteoarthritis = 4, ACTA2 aneurysm = 1, heritable non-syndromal aortopathy = 11). At 10 years follow-up, actuarial mean survivals were: aneurysm-osteoarthritis = 77.5 ± 10.4%; Loeys-Dietz = 90.0 ± 6.8%; Marfan = 94.6 ± 1.4%; heritable non-syndromal aortopathy = 95.9 ± 2.1% (NS). There were 60 aortic dissections (24 Type A, 36 Type B) during follow-up. At 10 years, survival free of dissection was comparable between groups: aneurysm-osteoarthritis = 90.7 ± 6.4%; Loeys-Dietz = 94.4 ± 5.4%; Marfan = 96.1 ± 1.2%; heritable non-syndromal aortopathy = 93.9 ± 2.3%, with similar findings at 20 years. Prophylactic aortic surgery was a first event during follow-up for 196 individuals (ACTA2 aneurysm = 3; aneurysm-osteoarthritis = 10; Loeys-Dietz = 19; Marfan = 119; heritable non-syndromal aortopathy = 45). A second surgical intervention was required in 45 individuals and a third intervention in 21 individuals. At 10 years follow-up, survival free of surgery differed between groups: aneurysm-osteoarthritis = 68.5 ± 10.1%; Loeys-Dietz = 40.8 ± 11.2%; Marfan = 75.5 ± 2.7%; heritable non-syndromal aortopathy = 63.8 ± 4.7% (p < 0.001). At 20 years follow-up mean survival free of surgery was: aneurysm-osteoarthritis = 26.6 ± 14.7%; Loeys-Dietz = 9.1 ± 8.2%; Marfan = 57.2 ± 3.4%; heritable non-syndromal aortopathy = 41.6 ± 8.2% (p < 0.001). Diagnosis of newer syndromic and non-syndromal heritable aortopathies is delayed compared to MFS, with associated complications of presentation with aortic dissection. Survival of individuals enrolled in follow-up surveillance is comparable between different genetic aortopathies, however aortic dissections still occur and need for surgical intervention is high.